2007
DOI: 10.1038/sj.onc.1210849
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between ATM and ATR in the regulation of common fragile site stability

Abstract: Common fragile sites are specific genomic loci that form constrictions and gaps on metaphase chromosomes under conditions that slow, but do not arrest, DNA replication. These sites have been shown to have a role in various chromosomal rearrangements in tumors. Different DNA damage response proteins were shown to regulate fragile site stability, including ataxia-telangiectasia and Rad3-related (ATR) and its effector Chk1. Here, we investigated the role of ataxia-telangiectasia mutated (ATM), the main transducer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 45 publications
(57 reference statements)
5
45
0
Order By: Relevance
“…Recent studies have revealed that the presence of AT-rich sequences in the region can form highly stable secondary structures promoting DNA breakage 24,25 . Of note, the ATM pathway-involved in the regulation of fragile sites 26 -was found to be significantly downregulated in our patients harbouring FGFR2 rearrangements, suggesting this pathway may play an important role in the occurrence of these fusion events in iCCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that the presence of AT-rich sequences in the region can form highly stable secondary structures promoting DNA breakage 24,25 . Of note, the ATM pathway-involved in the regulation of fragile sites 26 -was found to be significantly downregulated in our patients harbouring FGFR2 rearrangements, suggesting this pathway may play an important role in the occurrence of these fusion events in iCCA.…”
Section: Discussionmentioning
confidence: 99%
“…26). Interestingly, ATM pathway genes were found to be significantly downregulated in patients harbouring FGFR2 fusions as revealed by ssGSEA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fischer and co-workers reported similar findings in which hypoxia drives the formation of double minutes, fragile sites and anaphase bridges, which can lead to the development of gene (35) 10 (33) 26 (74) 30 (83) 12 (55) 19 (79) Intrachromosomal rearrangements* (%) 0 (0) 2 (7) 16 (46) 23 (64) 4 (18) 17 ( amplifications in glioblastoma (Fischer et al, 2008). A study by Ozeri-Galai and colleagues showed that both ATM and ATR kinases are involved in regulating the stability of fragile sites (Ozeri-Galai et al, 2008). Furthermore, they have shown that the induction of fragile sites by replication stress leads to formation of DNA-dsbs and activation of ATM, ATR and c-H2AX.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been documented to drive the fusion of double minutes into fragile sites, thereby generating homogenously staining regions (Coquelle et al, 1998). Fragile sites have been thought to be involved in DNAdsb-induced chromosomal aberrations (Ozeri-Galai et al, 2008). Fischer and co-workers reported similar findings in which hypoxia drives the formation of double minutes, fragile sites and anaphase bridges, which can lead to the development of gene (35) 10 (33) 26 (74) 30 (83) 12 (55) 19 (79) Intrachromosomal rearrangements* (%) 0 (0) 2 (7) 16 (46) 23 (64) 4 (18) 17 ( amplifications in glioblastoma (Fischer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several articles have reported that activated ERK regulates ATR activity (27,28,30). Although these findings are 1 Unpublished data.…”
Section: Cox-2 Induces Erk Activationmentioning
confidence: 63%